Molecular profiling for acromegaly treatment: a validation study. Issue 6 (June 2020) - Puig-Domingo, Manel; Gil, Joan; Sampedro-Nuñez, Miguel; Jordà, Mireia; Webb, Susan M; Serra, Guillermo; Pons, Laura; Salinas, Isabel; Blanco, Alberto; Marques-Pamies, Montserrat; Valassi, Elena; Picó, Antonio; et al.
Abstract : Pharmacologic treatment of acromegaly is currently based upon assay-error strategy, the first-generation somatostatin receptor ligands (SRL) being the first-line treatment. However, about 50% of patients do not respond adequately to SRL. Our objective was to evaluate the potential usefulness of different molecular markers as predictors of response to SRL. We used somatotropinoma tissue obtained after surgery from a national cohort of 100 acromegalic patients. Seventy-one patients were treated with SRL during at least 6 months under maximal therapeutic doses according to IGF1 values. We analyzed the expression of SSTR2, SSTR5, AIP, CDH1 (E-cadherin), MKI67 (Ki-67), KLK10, DRD2, ARRB1, GHRL, In1-Ghrelin, PLAGL1 and PEBP1 ( RKIP ) by RT-qPCR and mutations in GNAS gene by Sanger sequencing. The response to SRL was categorized as complete response (CR), partial (PR) or non-response (NR) if IGF1 was normal, between >2<3 SDS or >3 SDS IGF1 at 6 months of follow-up, respectively. From the 71 patients treated, there were 27 CR (38%), 18 PR (25%) and 26 NR (37%). SSTR2, Ki-67 and E-cadherin were associated with SRL response ( P < 0.03, P < 0.01 and P < 0.003, respectively). E-cadherin was the best discriminator for response prediction (AUC = 0.74, P < 0.02, PPV of 83.7%, NPV of 72.6%), which was validated at protein level. SSTR5 expression was higher in patients pre-treated with SRL before surgery. We conclude that somatotropinomas showed heterogeneity in the expression of genes associated with SRL response. E-cadherin was the best molecular predictor of response to SRL. Thus, the inclusion of E-cadherin in subsequent treatment-decision after surgical failure may be useful in acromegaly.